FROM LEARNING TO LEADING: THE IMPACT OF EDUCATION ON WOMEN’S EMPOWERMENT IN SHGs - Sardar Roy, Narayan; Chakraborty, Shnaoli (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Education is crucial in empowering women, enabling them to make informed decisions, challenge societal norms, and access resources. Educated women are more empowered than uneducated women (Barman, 2018). After joining SHGs (Self-Help Groups), women have experienced increased economic as well as social empowerment (Kundu, 2019). In this study, the researchers seek to endeavours the ramification of formal education on women’s social empowerment and personal transformation in SHGs. The quantitative survey study was finalised with a sample of 100 SHG members from Nilganj Gram Panchayet, North 24 PGS, West Bengal with the help of the Social Empowerment Scale (SES) and Personal Transformation Scale (PTS). The findings revealed that Formal Education Level positively 0.441 correlated with Social Empowerment and 0.478 correlated with Personal Transformation. It was suggested that the transformative role of Formal education may enhance communication skills, enabling women to interact more effectively with the community, educated women may be more likely to participate in societal activities, and formal education may increase awareness of government policies and schemes, enabling women to access resources and benefits, women with lower levels of formal education may face challenges in achieving personal transformation, particularly in Awareness of Human Rights and Self-Confidence, women with higher levels of formal education are more likely to achieve greater personal transformation.